ANALISIS FAKTOR PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOPI BUBUK CAP OBOR DI KOTA PONTIANAK - Jamaluddin, Jamaluddin; Dolorosa, Eva; Imelda, Imelda (Jurnal Sains Pertanian Equator, 2019)
The increasing of enthusiast drink coffee on the community has led to the company interest in splitting coffee products business. The presence of the companies in crushing coffee of course will give the effect on local coffee companies that is generally still small scale and have low competitiveness. One of Pontianak coffee products is a "˜Cap Obor"™. Compared with other, coffee products "˜Cap Obor"™ in the presentation impractical and do not have a variant taste. Even though, enthusiast of these product in Pontianak are still a lot of resulting that lead writer interested to researching. Buying decisions on coffe products "˜Cap Obor"™ are certainly inseparable from the factors that influence consumer behavior. The factors in question are personal factors (job, economic situation, lifestyle, personality and self-concept) and psychological factors (motivation, perception, the learning, confidence and attidudes). The purpose of this research is to know which factors are the most dominant influencing of purchasing decisions of coffee products "˜Cap Obor"™. This research uses a quantitative method of causal form. The sampling technique used was purposive sampling with accidental sampling approach and the total sample of 100 respondents. To analyze data using conjoint analysis with the help of SPSS 21.0 software. The results of the analysis in the research indicated that a motivation factors are the dominant factor in influencing the buying decisions of coffe products "˜Cap Obor"™ in Pontianak. An indicator on the influential motivation factors is product superiority, where consumers are encouraged by making a taste, aroma and density of coffee products "˜Cap Obor"™. Keywords : Conjoint analysis,Personal factor, Psychological factor, Buying decision, Coffe.